2021
DOI: 10.1109/access.2021.3071508
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of an Internet of Healthcare Things for Medical Monitoring Using M/M/c/K Queuing Models

Abstract: Due to the non-stop and rapid spreading of virus pandemics all over the world, traditional healthcare monitoring capabilities of hospitals and/or medical centers are under a severe over-load. Modern computing infrastructures with the harmony of various layers of computing paradigms (e.g., cloud/fog/edge computing) for healthcare monitoring are apparently the essential computing backbone that help access and process instantly the medical data of every single patient at the very edge of the healthcare system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Thus, the Internet of Things is not only concerned with devices connected all over the world but can also be specific to various fields depending on utilities. Some of the areas that have witnessed specific Internet of Things within their domain are Industrial IoT [9], Internet of Agricultural Things (IoAT) [10], Internet of Healthcare Things (IoHT) [11], [12], Internet of Medical Things (IoMT) [13]- [17], Internet of Nano Things (IoNT) [18], Internet of Robotics Things (IoRT) [19], [20], Internet of Drone Things (IoDT) [21], Internet of Underwater Things (IoUT) [22], blockchain and IoT [23], Social IoT [24], Green IoT [25]- [27], etc. Some of the recent areas that highlight the necessity of IoT are Next-Generation IoT [28], [29], Satellite IoT [30], Internet of nano things [31], Internet of underwater things [32], [33].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the Internet of Things is not only concerned with devices connected all over the world but can also be specific to various fields depending on utilities. Some of the areas that have witnessed specific Internet of Things within their domain are Industrial IoT [9], Internet of Agricultural Things (IoAT) [10], Internet of Healthcare Things (IoHT) [11], [12], Internet of Medical Things (IoMT) [13]- [17], Internet of Nano Things (IoNT) [18], Internet of Robotics Things (IoRT) [19], [20], Internet of Drone Things (IoDT) [21], Internet of Underwater Things (IoUT) [22], blockchain and IoT [23], Social IoT [24], Green IoT [25]- [27], etc. Some of the recent areas that highlight the necessity of IoT are Next-Generation IoT [28], [29], Satellite IoT [30], Internet of nano things [31], Internet of underwater things [32], [33].…”
Section: Related Workmentioning
confidence: 99%
“…However, the work did not elaborate the involvement of performance evaluation for such medical infrastructures. The works [ 2 , 28 ] studied different pure performance metrics of an Internet of Health Things (IoHT) such as mean response time (MRT), resource utilization, service throughput and so forth. Nevertheless, the evaluation of pure performance metrics without an appropriate consideration of failure modes is optimistic and, in some cases, it is not sufficient, for instance in the case of massive data transactions as in MIS.…”
Section: Related Workmentioning
confidence: 99%
“…The use of such an MIS is to improve the quality and effectiveness of healthcare services within and across hospitals and medical centers. The implementation of existing MIS often relies on an underlying sophisticated networked system associated with advanced computing paradigms (e.g., cloud/fog/edge computing) via dedicated communication links to remote data centers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors have indicated a future improvement to resolve slight fluctuations that result from randomness differential evolution optimization. Silva et al [37] proposed a queuing model to evaluate the performance of health monitoring in the context of IoHT. The evaluation included IoT sensors and edge, fog, and cloud components while estimating metrics such as mean response time, the utilization level, and mes-sage drop rate.…”
Section: Edge Computingmentioning
confidence: 99%